Swear Word in West Kalimantan Community - Martina; Lubis, Tasnim (Tradition and Modernity of Humanity, 2022)
West Kalimantan has to swear words that are considered unique in each region. The habit of using swear words that are usually done by the community is something that is considered taboo so far. However, swear words can contain negative and positive values, which are often said in everyday life. Swearing or swear a word is a form of venting for someone's frustration and disappointment that is buried in the heart because of an unpleasant situation. This study aimed to describe the forms of a swear words in the Malay language of West Kalimantan. The method used in this study was a qualitative descriptive method. The data was obtained through a literature review and direct interviews with engaging and taking notes. The study results showed that Malay cursing in West Kalimantan community is very varied and has local wisdom. Swear word in Malay is obtained in the form of references, namely state or nature, animal, body parts, activity, professional, and subtle creature.